The use of 17β Estradiol gel and progestogen tablet for hormone replacement therapy (HRT) in menopause (Medical Journal of Indonesia, 2003)
The treatment and prevention of disease in menopausal women due to deficiency of estrogen hormone are done through the administration of estrogen hormone, known as hormone replacement therapy (HRT). The administration of HRT is commonly done through the administration of tablets. However, the administration of tablet will result in metabolism in the colon and liver. Tablets are usually used on a daily basis such that it may lead to boredom and results in gastrointestinal disorder. The administration of gel, on the other hand, is done by applying the gel to the body and therefore metabolism in the colon and liver can be prevented. In women with uterus, estrogen must be combined with progestogen. The type of progestogen recommended is the one with natural derivative and which possesses antimineralocorticoid properties, such that fluid retention can be avoided. One of the types of progestogen which does not result in fluid retention is nomogestrol acetate. Nomogestrol acetate will also inhibit 17β hydrosisteroiddehydrogency enzyme type 1, such that estradiol (E2) is prevented from being transformed into estron (E1). As a result, E2 level in the breast tissue is kept at minimum, thereby reducing the risk of breast cancer. (Med J Indones 2003; 12: 194-8) Keywords: , ,,,